Comparison of Maxillary Occlusal Plane with Various Craniofacial Reference Lines in Nepalese and Indian Young Adults - Acharya, Binod (Orthodontic Journal of Nepal, 2011)
Orientation of occlusal plane for complete dentures play a vital role as it affects all the basic requirements of complete dentures. Depending on soft tissue landmarks for orienting occlusal plane seems to be unreliable. Cephalometrics were introduced in Prosthodontics to orient the occlusal plane in the same position as it was with the lost natural teeth. In the present study, 60 lateral cephalometric radiographs of a group of male and female dentulous subjects of Indian and Nepali origin (30 subjects in each group) were obtained and tracings were made. All the subjects selected were in the age group of 20-30 years in whom the facial growth was completed. Angular measurements were made between FH (Frankfort Horizontal plane)- CP (Camper's Plane), FH-OP (Occlusal Plane) and CP-OP and subjected to statistical analysis to determine the degree of separation between these planes in Indian and Nepalese ethnic groups. The absolute parallelism between the natural occlusal plane and Camper's plane were not proven in both Indian and Nepalese subjects involved in this study. This significantly reduces the reference values of these planes in Prosthodontics.